Within-Person Variability in First Impressions From Faces. (July 2021) - Gogan, Taylor; Beaudry, Jennifer; Oldmeadow, Julian
Perceptions of an individual can change dramatically across different images of their face. Questions remain as to whether some traits are more sensitive to image variability than others. To investigate this issue, we constructed a database of 340 naturalistic images consisting of 20 photos of 17 individuals. In this preregistered study, 95 participants rated all 340 images on one of three traits: trustworthiness, dominance, or attractiveness. Across images, participants' trustworthiness ratings tended to vary more than dominance, which in turn varied more than attractiveness; however, the relative differences between traits depended on the identity in question. Importantly, despite the variability in ratings within identities, there were substantial differences between individuals, suggesting that these trait judgements are based to some degree on relatively invariant facial characteristics. We found greater between-identity variability for attractiveness judgements compared to trustworthiness and dominance. Future research should further investigate the extent to which each trait dimension is tied to the identity of the faces.